Flexible and Configurable Embedded Electrical Energy Measurement System to Acquire and ProcessHigh-Frequency Features - Real, Gustavo Ernesto; Otero, Alejandro Daniel; Véliz, Maximiliano (Elsevier, 2023)
A novel High-Frequency Electric Energy Metering System to inspect non-conventional features that may be relevant for studying real-time energy disaggregation and control of household appliances is presented. Integration of a data acquisition and control board, designed and built to be assembled with an Arduino Due, with the M90E36A Demo Board, allows for flexible and configurable electrical energy measurements. A key feature is that up to 4 current channels can be measured synchronously. On the one hand, samples can be obtained and processed by the M90E36A IC internal Digital Signal Processor at 3 Hz in the time domain and 2 Hz in the frequency domain. On the other hand, the M90E36A IC direct access memory mode can be operated, allowing 8 kHz pure voltage and current signals to be obtained. Finally, integration with Raspberry Pi allows to design and incorporate a custom signal processor into the study. Additionally, in this article, an application example is presented where the variation of the residual harmonic components of a household appliance is obtained.
Keywords: Ingeniería y tecnología::Ingeniería eléctrica, Ingeniería electrónica